2009
DOI: 10.1002/art.24489
|View full text |Cite
|
Sign up to set email alerts
|

Altered mineralization of human osteoarthritic osteoblasts is attributable to abnormal type I collagen production

Abstract: Objective. Bone tissue in osteoarthritis (OA) is composed of abundant undermineralized osteoid matrix. The aim of this study was to investigate the mechanisms responsible for this abnormal matrix, using in vitro OA subchondral osteoblasts.Methods. Primary normal and OA osteoblasts were prepared from tibial plateaus. Phenotype was determined by alkaline phosphatase activity, and osteocalcin, osteopontin, prostaglandin E 2 (PGE 2 ), and transforming growth factor ␤1 (TGF␤1) were assessed by enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
119
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 55 publications
(96 reference statements)
15
119
0
2
Order By: Relevance
“…Twelve months post-ovariectomy, this ratio had increased significantly to 610 and thirty-one months following ovariectomy this ratio had almost doubled to 1100. Previously it has been demonstrated using osteoblast-like cells that COL1α2 expression did not vary when cells were exposed to a mineralising media, whereas COL1α1 expression, which was initially high, progressively declined, leading to a decrease in the COL1α1:COL1α2 ratio concomitant with an increase in mineralisation [34]. The current study found that an increase in the COL1α1:COL1α2 ratio is associated with a reduction in mineralisation in the metacarpal bone.…”
Section: Discussionsupporting
confidence: 55%
“…Twelve months post-ovariectomy, this ratio had increased significantly to 610 and thirty-one months following ovariectomy this ratio had almost doubled to 1100. Previously it has been demonstrated using osteoblast-like cells that COL1α2 expression did not vary when cells were exposed to a mineralising media, whereas COL1α1 expression, which was initially high, progressively declined, leading to a decrease in the COL1α1:COL1α2 ratio concomitant with an increase in mineralisation [34]. The current study found that an increase in the COL1α1:COL1α2 ratio is associated with a reduction in mineralisation in the metacarpal bone.…”
Section: Discussionsupporting
confidence: 55%
“…COL1 plays an important functional role during osteogenesis as it augments the cell adhesion and lays a foundation for OPN, OCN and bone matrix mineralization (21,22). OPN and OCN have high affinity of hydroxyapatite and can specifically integrate with the adhesion and connection of cells and tissues (23).…”
Section: Effect Of Tgfβ1 On the Expression Of Osteogenic Markers In Bmentioning
confidence: 99%
“…2). Osteoarthritis (OA) is a leading cause of morbidity in aging populations and is characterized by degradation and loss of cartilage, inflammation of the synovium, formation of osteophytes, and bone sclerosis (21). Type I collagen levels are elevated in the trabecular bone within the femoral heads of patients with OA, which can lead to an increase in mineralization (22).…”
Section: Resultsmentioning
confidence: 99%